Pengetahuan, sikap dan praktek kb mandiri wanita tidak menikah di DIY - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRAK The privatized family planning (FP) program has the potential of providing support to unmarried reproductive age women. These women will become more sexually active and will use private FP facilities. The results of the 1989 Privatized FP Survey in Yogyakarta indicated that their FP and its privatization knowledge, attitude and practice (KAP) were not very encouraging. Through public education and assistance to self-help community organizations the program will enhance the KAP of unmarried reproductive age women.